The Role of Physical Activity in Managing ADHD Symptoms in Children and Adolescents – Review of Current Literature - Chojnacka, Barbara; Ożga, Aleksandra; Wątor, Julia; Woźniacka, Agnieszka; Krzeszowiak, Jerzy; Boba, Barbara; Pulanecki, Tomasz; Podolska, Alicja; Bryksy, Sylwia; Kolano, Patrycja (Quality in Sport, 2025)
Abstract Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders seen in pediatric and adolescent psychiatry. The major symptoms are impulsivity, difficulties in sustaining attention and increased levels of motor activity. Emerging studies show that participating in physical activity may help improve ADHD symptoms. Aim of the study: This review explores the influence of physical activity on ADHD symptoms in children and adolescents. We also try to highlight the potential therapeutic role of physical activity as a complementary intervention in ADHD management. Materials and methods: An extensive search of the literature was performed in the PubMed database up to the year 2025. Conclusions: This review’s findings show that physical activity interventions benefit ADHD symptoms and executive functions in children and adolescents. Results of the studies showed that physical activity, especially organized closed-skill activities like running and aerobic training, enhanced the core ADHD symptoms (impulsivity, attention dysregulation, hyperactivity) the most, while open-skill activities that require real-time adaptation to environmental changes, had some effect on inhibitory control. What is more children and adolescents should participate in physical activities that they like in order to guarantee compliance and the durability of the intervention. Exercise should be included in the treatment plan for ADHD to offer holistic benefits, that not only addresses symptoms, but also enhances cognitive, behavioral, and emotional aspects of a child’s life. Future work should include longitudinal research to explore the effects of physical activity on ADHD symptoms and the development of individualized exercise interventions tailored to individual symptoms profiles. Keywords: „Attention deficit hyperactivity disorder”, „ADHD”, „Physical Activity”, „Exercises”, „Children”, „Adolescents”.